Stalin, Japan, and the Struggle for Supremacy over China, 1894–1945 - Hiroaki Kuromiya (Routledge, 2023)
Stalin was a master of deception, disinformation, and camouflage, by means of which he gained supremacy over China and defeated imperialism on Chinese soil. This book examines Stalin's covert operations in his hunt for supremacy. By the late 1920s Britain had ceded place to Japan as Stalin's main enemy in Asia. By seducing Japan deeply into China, Stalin successfully turned Japan's aggression into a weapon of its own destruction. The book examines Stalin's covert operations from the murder of the Manchurian warlord Zhang Zuolin in 1928 and the publication of the forged "Tanaka Memorial" in 1929, to Stalin's hidden role in Japan's invasion of Manchuria in 1931, the outbreak of all-out war between China and Japan in 1937, and Japan's defeat in 1945. In the shadow of these and other events we find Stalin and his secret operatives, including many Chinese and Japanese collaborators, most notably Zhang Xueliang and Kōmoto Daisaku, the self-professed assassin of Zhang Zuolin. The book challenges accounts of the turbulent history of inter-war East Asia that have ignored or minimized Stalin's presence and instead exposes and analyzes Stalin's secret modus operandi, modernized as "hybrid war" in today's Russia. The book is essential for students and specialists of Stalin, China, the Soviet Union, Japan, and East Asia.
Keywords: 320; Cold War; Iosif Stalin; Manchukuo; Manchuria; Mao Zedong; Marco Polo Bridge Incident; Ozaki Hotsumi; Sino-Japanese War; Soviet Union; Tanaka Giichi; Tanaka Memorial; USSR; Zhang Zuolin